Treatment options for isolated aortic valve insufficiency: a review - Argaw, Salem; Azizgolshani, Nasim; Blitzer, David; Takayama, Hiroo; George, Isaac; Pirelli, Luigi (Frontiers in Cardiovascular Medicine, 2024)
Aortic insufficiency (AI) is a valvular disease with increasing prevalence in older patients. The modern era provides numerous options for the management of AI which is explored here. Traditional interventions included aortic valve replacement with either mechanical or bioprosthetic aortic valves. While the former is known for its durability, it has grown out of favor due to the potential complications of anticoagulation. The preference for bioprosthetic valves is thus on the rise, especially with the advancements of transcatheter technology and the use of valve-in-valve therapy. Surgical options are also no longer limited to replacement but include complex techniques such as those required for aortic valve repair, Ozaki neocuspidization, Ross procedure and valve-sparring aortic root repair. Transcatheter options for the management of AI are not commercially available currently; however, preliminary data from ad-hoc trials, showed promising results and potential use of transcatheter technology in a variety of patients with pure AI.